Study on integrated bioseparation technologies for mass taxane production - Wang, Yuheng (University of Ottawa (Canada), 2004)
In this work, the principles of chemical engineering, plant biology, and phytochemistry were successfully applied to the separation of bioactive compounds from plant materials, taking the taxane extraction and purification as an example. A new model, the Solute Distribution Model, was proposed and used to guide the experimental work. Based on the model, two approaches, the Dual-Solvent Extraction approach and the ExtractionAdsorption approach, were developed in order to enhance both selectivity and recovery rate in bioseparation. Separation from Taxus Canadensis of all valuable products, including paclitaxel, 9-DHB III, 10-DAB III, Baccatin III, and other possible by-products, was studied experimentally. Dynamic Pressurized Liquid Extraction, a new extraction technique in the area of natural product mass production, was applied, along with conventional solvent extraction means. Based on the results of this work, the Solute Distribution Model, the Dual-Solvent Extraction approach and the Extraction-Adsorption approach were found to be effective tools for the development of cost-efficient and environmentally friendly technologies in large-scale production of valuable products from plant materials. One novel taxane extraction and purification process, integrated as DPLE-SPE-Chromatography, was invented and proofed. Certain interesting experimental phenomena, particular to the system examined, were observed and explained with fundamental principles. Compared to the reported results of previous studies, the newly developed process could potentially offer higher product yields, milder operating conditions, and lower negative environmental impacts and, therefore, better economics. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.